2002
DOI: 10.1002/pssb.200301537
|View full text |Cite
|
Sign up to set email alerts
|

N‐type (P, Sb) and p‐type (B) doping of hydrogenated amorphous Si by reactive rf co‐sputtering

Abstract: PACS 73.61. Jc, 78.30.Ly, 78.66.Jg, 81.05.Gc B, P or Sb were doped into amorphous silicon films by the reactive radio-frequency co-sputtering method. The targets used were composed of silicon wafers and small about 1 mm thick chips of the respective impurity element, which were attached to the silicon wafers with silver powder cement and epoxy resins. Argon and hydrogen partial pressures used were 5 × 10 −3 and 5 × 10 −4 torr, respectively. The impurity concentration in the film was determined by secondary ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…3,4) To understand the localization of electronic states, temperature dependence of conductivity data of amorphous silicon and related alloys have been analyzed with the help of various hopping models. [5][6][7][8][9] In the amorphous silicon, the electron conduction paths are composed of s-p hybrid orbitals and carrier transport is controlled by the nearest-neighbor hopping (NNH) or the variable-range hopping (VRH) conduction. 10) In this material, it was typically found that the activation energy of the electrical conductivity decreases progressively as the temperature falls.…”
Section: Introductionmentioning
confidence: 99%
“…3,4) To understand the localization of electronic states, temperature dependence of conductivity data of amorphous silicon and related alloys have been analyzed with the help of various hopping models. [5][6][7][8][9] In the amorphous silicon, the electron conduction paths are composed of s-p hybrid orbitals and carrier transport is controlled by the nearest-neighbor hopping (NNH) or the variable-range hopping (VRH) conduction. 10) In this material, it was typically found that the activation energy of the electrical conductivity decreases progressively as the temperature falls.…”
Section: Introductionmentioning
confidence: 99%
“…19) The well-known conduction mechanisms in semiconductors include band conduction, nearest-neighbor-hopping (NNH) conduction, 9,10,[20][21][22][23][24][25][26][27] and variable-range-hopping (VRH) conduction. [21][22][23][27][28][29][30][31][32] In the case that the currents due to band, NNH, and VRH conductions flow completely in parallel in the valence band, the Al acceptor level (E Al ), and the Fermi level [E F (T )], respectively, ρ(T ) can be expressed as…”
mentioning
confidence: 99%
“…The well-known conduction mechanisms in semiconductors include band conduction, NNH conduction, 9,10,[25][26][27][28][29][30][31][32] and VRH conduction. [26][27][28][32][33][34][35][36][37] If the currents due to band, NNH, and VRH conduction flow in parallel in the VB, at an Al acceptor level (E Al ), and around E F , respectively, the overall temperature-dependent resistivity [i.e. ρ(T)] can be expressed as…”
Section: Methodsmentioning
confidence: 99%
“…1. At (C Al − C N ) values of around 2 × 10 19 cm −3 in Fig.1, the ρ(300) values for the PVT-grown codoped samples are still slightly higher than those for the CVD-grown samples.Figure2shows Arrhenius plots of ρ(T) for the CVD-grown samples with C Al values of 2.4 × 10 19 and 3.4 × 10 19 cm −3 (▿ and ◯, respectively), and for the PVT-grown codoped sample with C Al of 3.0 × 10 19 cm −3 and C N of 2.9 × 10 18 cm −3 (•).The well-known conduction mechanisms in semiconductors include band conduction, NNH conduction,9,10,[25][26][27][28][29][30][31][32] and VRH conduction [26][27][28][32][33][34][35][36][37]. If the currents due to band, NNH, and VRH conduction flow in parallel in the VB, at an Al acceptor level (E Al ), and around E F , respectively, the overall temperature-dependent resistivity [i.e.…”
mentioning
confidence: 99%